Measurement of Temperature Distribution around a Vertical Fin by Mach-zehnder Interferometry. (2016) - Baby, Binoy; Anooplal, B.
Abstract: Interferometry is an optical non-intrusive technique becoming increasingly popular in the flow and heat transfer visualisation and measurement. In the present study, experimental investigation on heat transfer around an isothermal vertical fin using Mach-Zehnder Interferometry is carried out. The temperature of surrounding air, at a reference point, is recorded by a thermocouple placed at a distance from the heat source. Interference patterns are captured by a camera and analyzed using an image processing tool in MATLAB software. From the observations, it is pellucid that the change of air temperature in one path of the coherent laser beam results in the deformation of the interference pattern. By comparing the initial and deformed fringe patterns using the digital image processing technique, the temperature distribution around the heat source is obtained. The experimental values compared with the analytical results of vertical heated plate, show very good agreement. This indicates the reliability of interferometric measurement method.